Comparing legacy media responses to the changing business of news: Cross-national similarities and differences across media types - Cornia, A; Sehl, A; Nielsen, R (Sage Publications Ltd., 2018)
In this article, we analyse how legacy media organizations in six countries are adapting to the changing business of news. We focus on how similarities and differences in their responses to digital developments are shaped by the interplay between organizational legacy and national context. The study draws on media sociology and comparative media systems research and is based on 54 interviews with senior editors and managers at 25 newspapers and commercial broadcasters in Finland, France, Germany, Italy, Poland, and the UK. We find that organizations within the same medium respond to change in similar ways (newspapers versus broadcasters), and that these responses are surprisingly similar across different countries. We argue that factors related to the medium-specific legacy shape media adaptation more than do structural differences between national media systems because news organizations faced with a changing and uncertain environment imitate the strategies adopted by peer organizations elsewhere.